ATOMIC NUCLEUS AND ITS PHYSICAL PROPERTIES - Abduvasiyev Sardor; Qudratova Farog`at (Web of Journals Publishing, 2024)
This article provides an in-depth exploration of the physical properties of the atomic nucleus, including its structure, composition, and interactions. It covers key concepts in nuclear physics, examines relevant literature, discusses methodologies used in nuclear research, presents notable findings, and concludes with implications and suggestions for further study.
Keywords: Atomic nucleus, nuclear physics, nuclear properties, nucleon, nuclear forces, quantum mechanics.